Effect of a Multidimensional Pharmaceutical Care Intervention on Inhalation Technique in Patients with Asthma and COPD - Wanqing Wang; Tao Xu; Qiong Qin; Liyan Miao; Jian’an Bao; Rong Chen (Canadian Respiratory Journal)
Background. Inhalation therapy is the main treatment for asthma and chronic obstructive pulmonary disease (COPD) patients. Owing to the poor inhaler technique in using inhalers, we assessed the effect of a multidimensional pharmaceutical care on inhalation technique in patients with asthma and COPD. Materials and Methods. A 3-month controlled parallel-group study was undertaken in asthma and COPD patients using dry powder inhalers (DPIs). Patients in the intervention group received multidimensional pharmaceutical care, including establishment of a special dispensing window, face-to-face demonstration and education, brochure education, videos education, online consultation and education, and follow-up reeducation. Patients in the control group received usual pharmaceutical care. The inhaler technique score, correctness of inhaler usage, beliefs about medicines questionnaire (BMQ) score, asthma control test (ACT), and COPD assessment test (CAT) were measured pre- and postintervention. Quality of life improvement evaluated according to score changes of ACT in asthma and CAT in COPD and patient satisfaction were measured postintervention. Results. 259 patients finished the study with 133 in the intervention group and 126 in the control group. Compared to preintervention and control group postintervention, the inhaler technique score, correctness of inhaler usage, and ACT score significantly increased in the intervention group postintervention, while the BMQ score and CAT score decreased significantly P<0.05. Significant improvements in quality of life and patient satisfaction were found P<0.05. Conclusion. This study showed the multidimensional pharmaceutical care for asthma and COPD patients were effective in improving inhalation technique. By providing pharmaceutical care, pharmacists might help asthma and COPD patients to acquire better quality of life.